National Household Education Survey, 1991 ([Verlag nicht ermittelbar], 1993)
This data collection consists of two main components: the Early Childhood Education survey (children 3 to 8 years old) and the Adult Education survey (persons 16 and older). The Early Childhood Education component was designed to collect information on children's experiences in a range of settings, including their homes, child-care arrangements, early childhood education programs, and schools. Experiences covered include cognitive activities such as reading and learning letters, words, and numbers, developmental activities such as singing songs and arts and crafts, and entertainment activities such as games and sports, television viewing, and attendance at movies, plays, and concerts. The Adult Education Survey, the second component of this study, provides data on the characteristics of adult participants and nonparticipants in adult education programs and explores why some adults participate in these activities and others do not. Data in this component cover participation in the past three years or ever, and characteristics of adult education courses or activities including the course title, basic skills and training content, degree requirement fulfillment, sponsor-employer involvement and payment source, and the perceived benefits and barriers to participation of both participants (including part-time) and nonparticipants.